A Novel Method to Radiolabel Stealth Liposome through 1,2- dimyristoyl-sn-glycero-3-phosphoethanolamine-N-DTPA with 99mTc and Biological Evaluation (Journal of Analytical Oncology, 2013)
Purpose: To study surface technetium labeling of stealth DTPA-Liposomeand to evaluate its potential as a molecular imaging tracer for both normal and melanoma-bearing mice.The radiolabeling yield of liposomes was greater than 90%and showed good chemical and biological stability. Biodistribution studies in normal mice showed blood clearance with hepatic and renal depuration. Melanoma-bearing mice showed a similar pattern of biodistribution with high tumor uptake allowing tumor imaging.The developed method of surface radiolabeled DTPA-PEG-Liposomes with 99mTc was effective and stable in vivo.